Preheated machining in end milling of hardened steel AISI D2 - Lajis, M. A.; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Ginta, Turnad Lenggo; Patwari, Muhammed Anayet Ullah (2008)
This paper the outcome of a study on tool life and surface roughness of TiAlN coated carbide tools used in end milling of AISI D2 hardened steel under room temperature and preheated machining conditions. The tool life and surface roughness of TiAlN coated carbide tools was investigated at various combinations of cutting speed, feed and preheating temperature. Sufficient number of experiments was conducted based on the central composite design (CCD) which was adopted by response surface methodology (RSM) to generate tool life prediction values. Both first and second order quadratic models have been developed and the adequacy of the models were tested at 95% confidence interval. The effects of cutting conditions on tool life and tool wear morphology were also investigated. The experimental results show that preheated machining led to appreciable increasing tool life compared to room temperature machining. The percentage of tool life increase was between 190-315 % depending on preheating temperature. Preheating of the work material with higher heating temperatures (250-450 ºC) gives significant improvement in terms of tool life. Abrasive wear, attrition wear and diffusion wear are found to be a very prominent mechanism of tool wear. It has been observed that preheated machining of the material leads to surface roughness values well below 0.4 μm, such that the operations of grinding as well as polishing can be avoided at the higher cutting speeds.